Placental Chorangiosis: Increased Risk for Cesarean Section - Shariska S. Petersen; Raminder Khangura; Dmitry Davydov; Ziying Zhang; Roopina Sangha (Case Reports in Obstetrics and Gynecology)
We describe a patient with Class C diabetes who presented for nonstress testing at 36 weeks and 4 days of gestation with nonreassuring fetal heart tones (NRFHT) and oligohydramnios. Upon delivery, thrombosis of the umbilical cord was grossly noted. Pathological analysis of the placenta revealed chorangiosis, vascular congestion, and 40% occlusion of the umbilical vein. Chorangiosis is a vascular change of the placenta that involves the terminal chorionic villi. It has been proposed to result from longstanding, low-grade hypoxia in the placental tissue and has been associated with such conditions such as diabetes, intrauterine growth restriction (IUGR), and hypertensive conditions in pregnancy. To characterize chorangiosis and its associated obstetric outcomes we identified 61 cases of “chorangiosis” on placental pathology at Henry Ford Hospital from 2010 to 2015. Five of these cases were omitted due to lack of complete records. Among the 56 cases, the cesarean section rate was 51%, indicated in most cases for nonreassuring fetal status. Thus, we suggest that chorangiosis, a marker of chronic hypoxia, is associated with increased rates of cesarean sections for nonreassuring fetal status because of long standing hypoxia coupled with the stress of labor.